Impact of the SCARE guideline on the reporting of surgical case reports: A before and after study. (September 2017) - Agha, R.A.; Farwana, R.; Borrelli, M.R.; Tickunas, T.; Kusu-Orkar, T.; Millip, M.C.; Thavayogan, R.; Garner, J.; Orgill, D.P.
Abstract: Introduction: The SCARE guideline was developed in 2016 through an expert Delphi consensus exercise. It aimed to improve the quality of reporting of surgical case reports. The aim of this study was to assess the impact of introducing the SCARE guideline for surgical on reporting of case reports submitted to a single journal. Methods: A total of 20 case reports published in the International Journal of Surgery Case Reports (IJSCR) and Annals of Medicine and Surgery (AMS) in July and August 2016, prior to the introduction of the SCARE guideline (the pre-SCARE period), were randomly identified and scored against the SCARE criteria. Two independent teams performed the scoring giving a total score out of a theoretical maximum of 34 for each case report, the 'SCARE score' (expressed as a percentage). The scores for the two teams were then compared and consensus was reached to achieve a final sore set. This process was repeated for the January and February 2017 issues of the journal, post implementation of the guideline (the post-SCARE period). SCARE scores were compared between the pre- and post-SCARE periods. Results: The mean pre-SCARE score was 75.0% (standard deviation ± 6.29, Range 62–84), and the mean post-SCARE score was 82.6% (standard deviation ± 8.02, range 66–99), a 10% relative increase in compliance which was statistically significant (P < 0.001). The Cohen's Kappa score between teams A and B was 0.871, implying very substantial agreement. Conclusion: Implementation of the SCARE guideline resulted in a 10% improvement in the reporting quality of surgical case reports published in a single journal. Adherence to SCARE reporting guidelines by authors, reviewers and editors should be improved to boost reporting quality. Journals should develop their policies, submission processes and guide for authors to incorporate the guideline. Highlights: Adherence to the SCARE reporting guideline by authors, reviewers and editors should be improved to boost reporting quality. Journals publishing surgical case reports should consider incorporating the SCARE guideline within their submission process. Journals utilising the SCARE guideline may see a benefit in reporting quality. We have determined the criteria that are most frequently missed, providing a focus area for efforts going forward.